Application of magnetized MOF‐74 to phthalate esters extraction from Chinese liquor. Issue 8 (21st February 2019) - Wang, Tiefeng; Zhang, Ruiqi; Li, Di; Su, Ping; Yang, Yi
Abstract: In this study, magnetized MOF‐74 (Ni) was prepared using an ultrasound‐assisted synthesis method. This novel functional magnetic adsorbent was characterized using various techniques. Using the prepared material as adsorbents, a magnetic solid‐phase extraction method coupled with high‐performance liquid chromatography was proposed for determining four phthalate esters in Chinese liquor samples. The extraction parameters, including solution pH, adsorbent amount, extraction time, and eluent type and volume, were optimized. Under the optimized conditions, proposed method showed good linearity within the range of 1.53–200 μg/L for diphenyl phthalate, 2.03–200 μg/L for butyl benzyl phthalate, 7.02–200 μg/L for diamyl phthalate, and 6.03–200 μg/L for dicyclohexyl phthalate, with correlation coefficients > 0.9944, low limits of detection (0.46–2.10 μg/L, S/N = 3), and good extraction repeatability (relative standard deviations of 3.7%, n = 6). This method was successfully used to analyze phthalate esters in Chinese liquor samples with recoveries of 74.4–104.8%. Two phthalate esters were detected in two samples, both at concentrations that satisfied the Chinese national standard, indicating this method has practical application prospects. The extraction efficiency of this method was also compared with conventional solid‐phase extraction using commercial C18 cartridges. The results demonstrated that the proposed magnetic solid‐phase extraction is a simple, time‐saving, efficient, and low‐cost method.